The education word gap emerges by 18 months: findings from an Australian prospective study - Mary E. Brushe; John Lynch; Sheena Reilly; Edward Melhuish; Murthy N. Mittinty; Sally A. Brinkman (BMC, 2021)
Abstract Background The idea of the '30 million word gap' suggests families from more socioeconomically advantaged backgrounds engage in more verbal interactions with their child than disadvantaged families. Initial findings from the Language in Little Ones (LiLO) study up to 12 months showed no word gap between maternal education groups. Methods Families with either high or low maternal education were purposively recruited into a five-year prospective study. We report results from the first three waves of LiLO when children were 6, 12 and 18 months old. Day-long audio recordings, obtained using the Language Environment Analysis software, provided counts of adult words spoken to the child, child vocalizations and conversational turns. Results By the time children were 18 months old all three measures of talk were 0.5 to 0.7 SD higher among families with more education, but with large variation within education groups. Changes in talk from 6 to 18 months highlighted that families from low educated backgrounds were decreasing the amount they spoke to their children (− 4219.54, 95% CI -6054.13, − 2384.95), compared to families from high educated backgrounds who remained relatively stable across this age period (− 369.13, 95% CI − 2344.57, 1606.30). Conclusions The socioeconomic word gap emerges between 12 and 18 months of age. Interventions to enhance maternal communication, child vocalisations and vocabulary development should begin prior to 18 months.